PENGARUH VARIABEL DEMOGRAFI DAN PERSEPSI KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PRODUK HIJAU PHILIPS LED DI KOTA DENPASAR - Prawira Janitra, I Made Diksa; Satria Pramudana, Komang Agus (E-Jurnal Manajemen, 2016)
Increased awareness and responsibility of public health, making people decide to buy green products. However, there are still doubts about the quality of green products, so that consumers think to decide to buy the product. This study aims to determine the effect of demographic and the perception of the quality of products on product purchasing decisions Philips LED lights green. This research was conducted in the city of Denpasar. This study using purposive sampling technique. Methods of data collection using questionnaires with respondents as many as 120 are residents of Denpasar. Data were analyzed using dummy variable regression analysis. Based on the analysis states that demographic and perception of product quality influence on purchase decisions Philips LED lights green products.
Keywords: demography, product quality perception, purchase decision